Intracellular antibody capture technology: application to selection of intracellular antibodies recognising the BCR-ABL oncogenic protein. - Tse, E; Lobato, M; Forster, A; Tanaka, T; Chung, G; Rabbitts, T (2002)
The expression of antibodies inside cells to ablate protein function has the potential for disease therapy and for target validation in functional genomics. However, due to inefficient expression or folding, only a few antibodies or antibody fragments, usually as single-chain Fv antibody fragments (scFv), bind their antigens in an intracellular environment. We have established a genetic-selection technology (intracellular antibody capture, IAC) to facilitate the isolation of functional intracellular scFv from a diverse repertoire. This approach comprises an in vitro library screen with scFv-expressing bacteriophage, employing bacterially expressed antigen, followed by a yeast in vivo antibody-antigen interaction screen of the sub-library of in vitro scFv antigen-binders. Accordingly, we have isolated panels of scFv that bind intracellularly to the BCR or the ABL parts of the BCR-ABL oncogenic protein. Sequence analysis of the intracellular antibody scFv panels revealed a sequence conservation indicating an intracellular antibody consensus for both VH and VL, which could form the basis for the de novo synthesis of intracellular antibody libraries to be used with intracellular antibody-capture technology.